Oceanographic Indicators of Seasonal Variability in the Guajira Upwelling System and Their Relationship with Phytoplankton - Jhon Carlos Salon-Barros; Rafael Ricardo Torres-Parra; Digna Rueda-Roa; Frank Muller-Karger (Oceans, 2026)
The Guajira Upwelling System (GUS) is located between 10–12.5° N and 61–75.5° W in the Southern–Central Caribbean Sea. This study examines its spatial and seasonal variability using upwelling indices derived from surface differences in temperature, salinity, density, and absolute dynamic topography between the GUS and a nearby Caribbean region (78–68° W, 10–16° N) not affected by coastal upwelling. Weekly time series from 1998 to 2022 were analyzed. The difference-based indices were compared with Ekman transport, a conventional proxy for upwelling intensity, and with satellite-derived chlorophyll-a to evaluate the phytoplankton response. Seasonal cycles were further examined at four representative grid points along the system. Among the indices, sea surface temperature most effectively delineated the spatial extent and seasonal variability of the GUS. Comparisons with chlorophyll-a revealed a strong upwelling–biomass relationship in the northern sector (east of 73.5° W), whereas productivity in the southern sector was not primarily driven by coastal upwelling. Correlation maps indicated that the weakening of upwelling influence coincided with the region affected by the Magdalena River plume.